Pembelajaran Mengidentifikasi Nilai-Nilai Kehidupan Dalam Teks Cerita Pendek Dengan Menggunakan Model Discovery Learning Berorientasi Pada Kemampuan Berpikir Kritis Peserta Didik Kelas XI SMA Negeri 3 Cimahi Tahun Pelajaran 2022/2023 - Aira Salma Azahra; Titin Nurhayatin; Meity Suratiningsih (Lembaga Pengembangan Kinerja Dosen, 2023)
The low ability of students in identifying life values ​​in short story texts is the background of this research. One of the causes of this is the lack of use of appropriate learning models by educators. In addition, as a result of the lack of utilization of appropriate learning models, namely the low level of students' critical thinking skills. The purpose of this study was to examine the effectiveness of the Discovery Learning model in learning to identify life values ​​in short story texts. This study also aims to examine the effectiveness of the Discovery Learning model in improving students' critical thinking skills. As well as examining differences in students' abilities in identifying life values ​​in short story texts and differences in students' critical thinking abilities in the experimental class using the Discovery Learning model and the control class using the discussion method. The method used in this research is a quasi-experimental method with nonequivalent control group design. The results of the research are based on the Wilcoxon test of the Asymp value. Sig. (2-tailed) of 0.000 < 0.05. That is, it can be concluded that there are differences in the learning outcomes of students identifying life values ​​in short story texts between the experimental class using the Discovery Learning model and the control class using the discussion method. As for the results of the Mann-Whitney test, the Asymp value. Sig. (2-tailed) of 0.000 < 0.05. That is, the Discovery Learning model is effectively used in learning to identify life values ​​in short story texts. Then the results of calculating the average value of students' critical thinking skills in the experimental class using the Discovery Learning model are 3.7 and in the control class using the discussion method namely 3.4. That is, it can be concluded that there are differences in students' critical thinking abilities. This shows that the Discovery Learning model is effective in improving students' critical thinking skills.